EFEKTIVITAS PELAKSANAAN PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM PENGUATAN KELUARGA OLEH YAYASAN SOS CHILDREN’S VILLAGE MEDAN DI LINGKUNGAN III KELURAHAN NAMO GAJAH KECAMATAN MEDAN TUNTUNGAN - Windy Safutry (Welfare StatE, 2013)
Family is the most important unit in society as the main foundation for building quality human resources. The problems that occur in the community due to the weakness of the family institution. Seeing family especially economically disadvantaged feared to neglect the rights and needs of their children to be able to evolve like as a child. Therefore, through family strengthening programs are based on community empowerment, SOS Children's Villages Medan help families less fortunate families to make quality and independent in the long run. This study aims to determine the extent to which the effectiveness of the implementation of community empowerment through family strengthening programs by foundations SOS Children's Village Medan in Environment III Village Namo Gajah District Medan Tuntungan. This type of research used in this research is descriptive research type . The resident population is urban research Village Namo Gajah are listed as members of the family strengthening program , amounting to 36 people . Meanwhile , the data analysis techniques in this study using a single table and explained qualitatively by a Likert scale . Conclusions were obtained through analysis of the data that the effective implementation of community empowerment through family strengthening programs by foundations SOS Children 's Village Medan in Environment III Village Namo Gajah District Medan Tuntungan is effective . The calculation result is said to be affective from several measurements that have been done on understanding the program as much as 0.47 , 0.46 of targeting accuracy , timeliness as of 0.53 , from 0.61 as the achievement of objectives , and of real change as much as 0 , 34 . Keywords : Effectiveness, Community Empowerment, Family Strengthening Programs